Factors Influencing the Seasonal Flux of the Varved Sediments of Kusai Lake on the Northern Tibetan Plateau During the Last ∼2280 years - Zhang, Qi; Liu, Xingqi; Feng, Shengnan (Frontiers in Earth Science, 2022)
The varved sediments of Kusai Lake on the northern TP are rhythmically laminated with the interaction of dark and light layers formed during winter and summer within a year. This provides opportunities to explore the seasonal fluxes of varves and, thus, assess the potential for annual-resolution climate reconstruction. Here, we define a season index (SI) based on the difference in thickness between the light and dark layers, to evaluate the factors influencing the seasonal flux of varved Kusai Lake sediments. A positive SI represents more summer flux, and a negative SI indicates more winter flux. The results showed that the summer flux was higher than the winter flux in most of the last 2280 years. The summer flux had periodicities of approximately 2.3-2.9 years, 27 years, and 99 years at the 99% confidence level and approximately 15-16 years, 36 years and 285 years at the 95% confidence level, indicating that summer flux is affected mainly by solar activity (Gleissberg and 350 unnamed cycle) at centennial scales, by the Pacific Decadal Oscillation (PDO with a period of 15-25 years) at decadal scales, and by the Quasi-biennial Oscillation (QBO with a period of 2-3 years) at interannual scales. Noticeable increasing spikes of high winter flux corresponded well to lower solar activity and stronger Siberian high pressure (SH). The periods of high and low winter flux are generally related to the negative and positive phases of the North Atlantic Oscillation (NAO) and Atlantic Multidecadal Oscillation (AMO), respectively, during the last 1000 years.